2008
DOI: 10.4049/jimmunol.180.9.6094
|View full text |Cite
|
Sign up to set email alerts
|

Antigen Receptor Editing in Anti-DNA Transitional B Cells Deficient for Surface IgM

Abstract: In response to encounter with self-Ag, autoreactive B cells may undergo secondary L chain gene rearrangement (receptor editing) and change the specificity of their Ag receptor. Knowing at what differentiative stage(s) developing B cells undergo receptor editing is important for understanding how self-reactive B cells are regulated. In this study, in mice with Ig transgenes coding for anti-self (DNA) Ab, we report dsDNA breaks indicative of ongoing secondary L chain rearrangement not only in bone marrow cells w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(37 citation statements)
references
References 85 publications
4
33
0
Order By: Relevance
“…Finally, it could be argued that the lack of serum IgM in 2F5 V H +/+ mice is due to the 2F5 HCs inability to pair with LCs similar to the phenotype reported in κ+λ LC-deficient mice, which make no serum IgM but have detectable serum IgG composed of HC dimers (35) gized through receptor engagement (29,30). A similar IgM lo phenotype has also been described in splenic transitional B cells in the various 3H9 mouse lines (21,23,25,26,28), reflecting frequent anergic B cells, or alternatively, cells that have undergone LC editing (28,36,37). Interestingly, 2F5 V H +/+ mature B cells also exhibit lower sIgM densities, similar to anergic anti-Sm transgenic mature B cell fractions (38).…”
Section: Discussionsupporting
confidence: 60%
“…Finally, it could be argued that the lack of serum IgM in 2F5 V H +/+ mice is due to the 2F5 HCs inability to pair with LCs similar to the phenotype reported in κ+λ LC-deficient mice, which make no serum IgM but have detectable serum IgG composed of HC dimers (35) gized through receptor engagement (29,30). A similar IgM lo phenotype has also been described in splenic transitional B cells in the various 3H9 mouse lines (21,23,25,26,28), reflecting frequent anergic B cells, or alternatively, cells that have undergone LC editing (28,36,37). Interestingly, 2F5 V H +/+ mature B cells also exhibit lower sIgM densities, similar to anergic anti-Sm transgenic mature B cell fractions (38).…”
Section: Discussionsupporting
confidence: 60%
“…2B,C). These subsets have been reported as anergic self reactive B cells (Merrell et al, 2006; Kiefer et al, 2008). On the other hand, BAFF/3H9 mice had a lower proportion of CD93 hi B cells (2.0%) and 44.9% of these cells had a T2 phenotype (B220 + CD93 hi IgM high CD23 high ) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although Jκbias has been interpreted in the context of receptor editing, it is unclear if BAFF can act directly on editing-competent B cells because they respond poorly to BAFF and have little BAFF-R expression (Rolink et al, 2002; Hsu et al, 2002). Bosma and colleagues working with the 3H9-56R model have suggested that a small splenic B cell subset that they call T3′ might include autoreactive cells in the process of editing (Kiefer et al, 2008). T3′ cells had markers reminiscent of putative natural anergic B cells (T3 cells), though they lacked expression of CD23.…”
Section: Discussionmentioning
confidence: 99%
“…33 Receptor editing initiated in response to autoantigen exposure is thought to occur primarily during the immature/transitional T1 stage of B-cell development. 34,35 We speculate that a stochastic mutation which impairs receptor editing induced in response to selfreactivity may enforce B-cell autoreactivity. Based on our previous work showing that dnRAG1 mice accumulate CD5 1 B cells without progressing to overt CLL, 12 we propose that autoreactivity enforced by a receptor editing defect could permit continued autoantigenic stimulation, and thereby promote sustained CD5 expression and persistence of a CD5 1 B-cell clone.…”
mentioning
confidence: 98%